PENGEMBANGAN MODEL PEMBELAJARAN PAI INKLUSIF: TRANSFORMASI NILAI MODERASI MENJADI KARAKTER KEBANGSAAN SISWA - Nurjaya Nurjaya; Abdul Muhyi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Today, the world of education faces significant challenges in the form of the strengthening of religious exclusivism and intolerance among students due to the rapid flow of unfiltered information on social media. This study aims to analyze the process of internalizing the values ​​of moderation in Islamic Religious Education (PAI) learning, identify factors inhibiting the strengthening of national character, and formulate an effective inclusive PAI learning model at MAN Palopo City. The method used is descriptive qualitative with the researcher as the key instrument. Data were collected through observation, in-depth interviews with the Madrasah Principal, PAI teachers, and students, and curriculum documentation. Data analysis follows the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results show that the transformation of moderation values ​​is carried out through the integration of three domains: cognitive (contextual understanding), affective (empathy development), and psychomotor (real action). The novelty of this study lies in the use of digital media as a means of disseminating moderation that transforms students from content consumers to producers of peace narratives. The research conclusion confirms that the inclusive Islamic Religious Education (PAI) learning model supported by an egalitarian school culture is able to transform the value of moderation into a strong national character, thereby creating a generation that is both nationalistic and religious in the digital era.